Impacts of an invasive species (Anolis sagrei) on social and spatial behaviours of a native congener (Anolis carolinensis). (January 2022) - Bush, Jordan M.; Ellison, Michael; Simberloff, Daniel
Abstract : Interspecific aggression has important fitness consequences across the animal kingdom and can be especially important during species invasions, where asymmetric interactions between native and invasive species can lead to native species declines. We investigated the immediate behavioural consequences of interspecific interactions for a native species, the green anole lizard, Anolis carolinensis, after an invasion by a closely related invasive species, the Cuban brown anole, Anolis sagrei . We housed captive populations of green anoles (6 males, 6 females) in large outdoor enclosures and recorded their display behaviours (displays/min), activity levels (movements/min) and habitat use (2D and 3D home range size, perch height) for 10 days. We then introduced brown anoles and recorded the green anoles' behaviours for another 10 days, seeking differences between pre- and post-invasion behaviours. We recorded behavioural interactions between individuals (i.e. headbob and dewlap displays, chases, mating attempts, fights and copulations) throughout the study. To serve as a density control, we duplicated the experiment in a second enclosure using green anoles as 'invaders'. We performed the experiment eight times with two densities of invaders: high (4 males, 4 females) and low (2 males, 2 females). We found that green anoles have smaller two-dimensional and three-dimensional home ranges and higher average perch heights after invasions but that these changes resulted from increased population densities rather than aggression from brown anole invaders. Furthermore, although green and brown anoles did display to each other, both species preferentially interacted with conspecifics and escalated aggressive behaviours between the two species (e.g. lock-jawed fights) rarely occurred. Taken together, these findings indicate that high brown anole population densities, rather than direct interference competition, could be driving green anole displacement across the brown anole's invasive range. Highlights: Invasive brown anoles are thought to be aggressive towards native green anoles. We 'invaded' captive populations of green anoles with brown anoles. Changes in green anole behaviours after invasions were linked to invader density. Green and brown anoles engaged in few escalated aggressive interactions. High brown anole densities, not aggression, may be driving green anole declines.